Efeitos cardiorrespiratório e analgésico da anestesia intravenosa contínua com propofol e remifentanil em cães após medicação pré-anestésica com acepromazina - Gimenes, André Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
O objetivo deste estudo foi investigar os efeitos clínicos e cardiopulmonares do propofol associado ao remifentanil, infundido em três diferentes doses, para a manutenção anestésica em cães pré-medicados com acepromazina. Doze cães adultos, fêmeas, pesando 18.2±2.8 kg, foram empregados. Os cães foram pré-medicados com acepromazina (0,05 mg/kg via IV), seguida da indução anestésica com propofol (5 mg/kg IV). A manutenção anestésica foi realizada com propofol (0,2 mg/kg/min. IV), e remifentanil administrado pela via intravenosa, de acordo com os grupos: A (0,125 μg/kg/min), B (0,25 μg/kg/min) e C (0,5 μg/kg/min). Ambos os fármacos foram infundidos durante 120 minutos. Os mesmos cães foram anestesiados com todas as três doses de remifentanil, com intervalos de uma semana, usando uma seqüência aleatória e protocolo do tipo “estudo encoberto”. Ventilação artificial foi adotada durante todo o período de manutenção anestésica, para manter os valores de ETCO2 entre 35 a 40 mmHg. FC, PA, f, Vt, Vm, ETCO2, SpO2, pHa, hemogasometria e temperatura retal foram mensurados antes da indução e 5, 15, 30, 45, 60, 75, 90 e 120 minutos após a indução. A analgesia foi investigada por estímulo elétrico (50 mA, 5Hz, 60s), aplicado na margem sub-gengival do dente canino superior. Amostras de sangue foram coletadas para a dosagem de cortisol plasmático. A análise estatística das variáveis quantitativas foi realizada pelo método de Análise de Variância segundo o delineamento “cross-over” (p<0.05)... .

The aim of this study was to investigate the cardiopulmonary and clinical effects of propofol associated with remifentanil, infused in three doses, for anaesthesia maintenance in dogs premedicated with acepromazine. Twelve female adult mixed-breed dogs, mean weight 18.2 2.8 kg, were used. Dogs were premedicated with acepromazine (0.05 mg/kg IV) followed by induction of anaesthesia with propofol (5 mg/kg IV). Anaesthesia maintenance was performed with propofol (0.2 mg/kg/min. IV), and remifentanil infused as follows: A - 0.125 æg/kg/min, B - 0.25 æg/kg/min and C - 0.5 æg/kg/min. Both drugs were administered during 120 minutes. The same dogs were anaesthetised with all three doses of remifentanil in an one-week interval using a randomised Latin square design and a blind protocol. Artificial ventilation (O2: 20ml/kg) was carried out during anaesthesia to maintain the ETCO2 between 35 to 40 mmHg. HR, BP, RR, Vt, Vm, ETCO2, SpO2, pHa, blood gases, rectal temperature were measured before and 5, 15, 30, 45, 60, 75, 90 and 120 minutes after induction. Analgesia was investigated by electrical stimulus (50 mA, 5Hz, 60s) applied in gingival margin of superior canine tooth. Blood samples were collected for cortisol plasma measurements. Statistical analysis was performed by Variance analysis in a crossing-over design (p<0.05). HR decreased during anaesthesia according to the remifentanil dose, and increased significantly right after the end of infusion in all groups. MABP remained stable during anaesthesia (72-98 mmHg). Analgesia was proportional to remifentanil dose, and was adequate in B and C with no pain response in 11/12 dogs (91,7%), from 30 and 15 minutes of infusion respectively. Plasma cortisol levels decreased during anaesthesia in all groups. Anaesthesia recovery was smooth and fast in all dogs (26.4l4.3 to 33.3l6.3 min). On the second... (Complete abstract, click electronic address below).
Keywords: Anestesia intravenosa; Anestesia veterinaria - Cão